Soy protein - Rodrigues, Célia Fortuna (2015)
Soy protein products such as flour, concentrates and isolates are used in the food industry because of their functionality, nutritional value and low cost. This chapter presents an overview current knowledge of soy proteins, manufacture processes and modifications. The health benefits attributed to soy proteins are alsodiscussed. In addition the biomedical applications are summarized.